Selective Imidazoline Receptor Agonists: redefining the role of centrally acting agents in management of hypertension - Shetty, Sadanand; Bhoraskar, Anil; Mohan, J. C.; Chafekar, Deodatta; Tripathi, K.; Sivalingam, M.; Desai, Bhupen; Gude, Dilip; Sridhar, G.; Varghese, Chacko; Shah, V. T.; Dargad, Ramesh (International Journal of Advances in Medicine, 2019)
Hypertension, often referred to as ‘The silent killer’, is christened so, as it is seldom preceded by any warning signs or symptoms. With the new ACC/AHA guidelines lowering the Blood Pressure (BP) threshold values, it has resulted in a 140% relative increase in the hypertension prevalence in India, which is 3 times higher than that of in United States. Imidazoline receptor agonists control BP effectively with minimal adverse effects of sedation and mental depression that are usually associated with centrally acting antihypertensives. While having a low affinity to the α2-adrenergic receptors, these new generation centrally acting antihypertensive agents are highly selective for imidazoline receptor. Moxonidine, a second-generation centrally acting antihypertensive drug having selective agonist activity on imidazoline I1 receptors and minor activity on imidazoline α2 adrenoceptors, reduces the activity of Sympathetic Nervous System (SNS) by activating I1 imidazoline receptors in Rostral Ventrolateral Medulla (RVLM). Studies of moxonidine have shown equal effectiveness in lowering BP like other well-established antihypertensive drugs such as nifedipine, atenolol or angiotensin-converting enzyme inhibitors, with minimal adverse events. At doses of 0.2-0.6 mg, moxonidine induces satisfactory BP reduction in patients with mild-to-moderate essential hypertension. In patients with mild-to-moderate hypertension, moxonidine (0.2-0.4 mg o.d.) significantly decreased Systolic Blood Pressure/Diastolic Blood Pressure (SBP/DBP), respectively, by 19.5/11.6 mmHg. In obese, non-controlled hypertensive patients, there is a 14% and 13.5% reduction in the mean SBP and DBP, respectively, from the baseline value after moxonidine treatment and during the follow-up with an additional reduction in body weight, plasma leptin levels and Body Mass Index (BMI) (p<0.01). Thus, moxonidine could be considered as a therapeutic option in obese patients with metabolic syndrome.